Subarachnoid hemorrhage as a complication associated with thrombolysis in a patient with ischemic stroke. - Rojas-Benites, Mayra (2022)
Subarachnoid hemorrhage is a very rare complication of thrombolytic therapy. We report the case of a 76-year- old mestizo woman with a pacemaker, admitted to the emergency room due to compromised consciousness, walking difficulties and dysarthria. She reported a history of poorly controlled hypertension, hypothyroidism, and numerous surgical interventions. Based on a non-contrast Multislice Computed Tomography (MSCT) of the brain and the clinical manifestations, a diagnosis of ischemic stroke was established. Thrombolytic therapy with alteplase was immediately started and another non-contrast MSCT brain scan, performed three hours later, identified a subarachnoid hemorrhage as a treatment complication. Twenty-four hours later, a CT angiography confirmed an ischaemic stroke with hemorrhagic transformation, without the presence of a ruptured aneurysm. The patient was admitted to ICU, remaining in observation with permanent control of vital signs, and discharged after 20 days. the patient was discharged. The identification and reporting of this unusual complication contribute to a better understanding and diagnosis of the case.